The long-term added value of voiding school for children with refractory non-neurogenic overactive bladder: an inpatient bladder rehabilitation program. Issue 3 (June 2020) - Dossche, L.; Snauwaert, E.; Renson, C.; Van daele, J.; Raes, A.; Dehoorne, J.; Roels, S.P.; Van Laecke, E.; Van Herzeele, C.; Hoebeke, P.; Vande Walle, J.
Summary: Introduction & background: Despite adequate management, 20% of children with overactive bladder (OAB) syndrome fail to improve their bladder function. To approach the need for alternative strategies, an inpatient bladder rehabilitation 'voiding school' program was established. Objective: The objective of this study was to evaluate the short- and long-term (1-year follow-up) outcome of this voiding school program in children with refractory OAB. In addition, the authors aimed to identify which children achieved the best outcomes with this voiding school program. Study design: The charts of all children ( n = 357, mean age: 9.7 ± 2.0 years, 63.6% boys) with refractory OAB who attended voiding school between 2000 and 2010 were reviewed. A linear mixed model with random intercept was used to evaluate the incontinence (expressed by enuresis and daytime incontinence voiding scores) and maximal voiding volume (MVV). Results & discussion: This study demonstrated an overall beneficial long-term effect of the inpatient program on day- and night-time incontinence, in which 36.6% of children achieved dryness during day- and night-time. In addition, the mean overall decline in the number of wet nights and days declined with 4 extra dry days and/or nights per week, in comparison with the level of continence before attending the voiding school program. In contrast, only a temporary increase in MVV was seen, however, without relapse incontinence. At last, the authors identified the negative impact of decreasing age, male sex, dysfunctional voiding and nocturnal polyuria on the overall outcome of the inpatient program. Conclusion: An inpatient rehabilitation 'voiding school' program is a successful and safe treatment modality for children with refractory OAB that results in long-term significant increase of continence, as well as amelioration in degree of severity. The worst outcomes of this voiding school program were detected in children with young age, who were boys, or had associated nocturnal polyuria, dysfunctional voiding, and/or faecal incontinence. Summary Figure Schematic view of the voiding school program. At the 1st consultation, every child received a clinical examination, detailed history, micturition questionnaire, bladder diary to record drinking and voiding habits, kidney and bladder ultrasound, urine analysis, renal concentration test and uroflowmetry. The voiding school consisted of a first inpatient period of 5 days. This was followed by a two weeks interval with two ambulatory sessions. Then, the children started a second inpatient period of 5 days. Data have been collected at first consultation at Ghent University Hospital, entry and completion of the voiding school and 3, 6 and 12 months' follow-up. Summary Figure